A Tale of Two Programs : Assessing Treatment and Control in NREGA Studies - Bahal, Girish (World Bank, Washington, DC, 2021)
This paper revisits impact evaluation studies on the largest public workfare in the world, NREGA. In an environment where randomization is not feasible, I show why an impact evaluation exercise on NREGA should acknowledge the existence of an older program, SGRY. Using novel district-level expenditure data on SGRY, this article shows how ignoring the older program is likely to underestimate the general equilibrium impact of the employment policy on various relevant socio-economic outcomes. In most cases, ignoring SGRY underestimates NREGA’s impact by 30–40 percent.